Singing Your Way to Clarity: The Power of English Songs in Enhancing Pronunciation and Motivation among EFL Learners - Majid, Ahmad Risal; Atmaranie Dewi Purnama; Sam Hermansyah (Universitas Muhammadiyah Enrekang, 2026)
This study aimed to investigate the effectiveness of English songs in enhancing pronunciation skills and boosting learning motivation among EFL learners. The research was conducted using a mixed-methods approach at SMPN 1 Panca Rijang in the academic year 2024/2025. A total of 22 ninth-grade students participated in the study. Quantitative data were obtained through pronunciation pre-test and post-test assessments, while qualitative data were collected from semi-structured interviews with five students who achieved the highest post-test scores. The quantitative analysis was performed using descriptive statistics and a paired-sample t-test. The results showed a significant improvement in students’ pronunciation performance, with the mean score increasing from 8.18 in the pre-test to 12.91 in the post-test (mean difference = 4.727, t(21) = 18.44, p = 1.89 × 10⁻¹⁴). Since the p-value was far below the 0.05 significance level, the null hypothesis was rejected, confirming that English songs significantly enhanced students’ pronunciation skills. Qualitative findings revealed strong positive responses and high motivation among the students. Participants stated that learning pronunciation through songs was more enjoyable, easier to follow, and highly motivating. They also mentioned that the rhythm and repetition in the songs helped them imitate native-like pronunciation with greater confidence and reduced anxiety. In conclusion, English songs serve as a powerful, engaging, and effective pedagogical tool that simultaneously improves pronunciation accuracy and increases students’ motivation in EFL classrooms. This study recommends the integration of songs as an innovative strategy for pronunciation instruction.